100. Epidemiology of Mandibular Fracture Cases for Mataram University General Surgery Resident Competence in Hospital Education Center - Putra, Dhany Pratama; Istikharoh, Umu (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Introduction : WHO (2024) estimates that 20–50 million individuals get non-fatal injuries and over 1.2 million people globally pass away on traffic accidents. craniomaxillofacial fracture cases can be done by multidisciplinary, depend on diagnosis and competence of surgeons. Methods : This study is quantitative descriptive study using medical record data of craniofacial trauma patients NTB Province General Hospital from January 2022 to September 2024, patients who experienced or who had been diagnosed of craniofacial trauma. Results : 388 patients were diagnosed with craniofacial trauma at NTB Province Hospital. There were had 99 lower face fractures, 120 mid face fractures, and 169 with upper face fractures. It was found male gender was more than female, age range of 21-30 years. the 99 patients with mandibular fractures, 66 simple mandibular fractures obtained that could be done by  general surgery resident. In 2022-2023, Unram general surgery residents are not yet in the advanced surgical phase, cannot participate in mandibular fracture surgery. But this data can provide an overview that mandibular fracture cases are sufficient in number for they operative cases. Conclusions : This study, there are 66 cases of mandibular os fracture that can be performed operatively by unram general surgery residents according to competence of general surgeons as stated in the Decree Minister of Health. So that can help in help cranio maxilo facial cases in good interdisciplinary cooperation to get optimal results.